Kidney transplant outcomes in HLA desensitized patients with pretransplant CDC and/or FCM positive crossmatches - Noble, Johan; Dard, Céline; Giovannini, Diane; Naciri Bennani, Hamza; Fournier, Pierre; Bardy, Béatrice; Bourdin, Anne; Imerzoukene, Farida; Motte, Lionel; Terrec, Florian; Malvezzi, Paolo; Jouve, Thomas; et al. (Frontiers in Immunology, 2025)
BackgroundKidney transplant (KT) candidates with very high calculated panel reactive alloantibody (cPRA >95%) have limited chances to receive an HLA-matched transplant unless they undergo pretransplant desensitization.ObjectiveTo assess the efficacy of immunoadsorption (IA) in desensitizing pretransplant KT candidates with high cPRA and positive crossmatch.Materials and methodsThis was a single-center retrospective cohort study involving highly HLA-sensitized patients (cPRA >85%). Forty-nine patients underwent HLA-incompatible (HLAi) KT, of whom 25 (51%) received kidneys from deceased donors. Of these 49 patients, 23 had either a positive complement-dependent cytotoxic cross-match (CDC) and/or a positive flow cytometry cross-match (FCM). The remaining 26 patients had donor-specific anti-HLA (DSAs) detectable only by Luminex (CDC and FCM cross-matches were negative). Only CDC-positive and FCM-positive patients were desensitized. These 49 patients were compared with 160 patients who had cPRA >85% but underwent HLA-compatible (HLAc) KT, i.e., without pretransplant DSAs.Pretransplant desensitization included IA sessions, rituximab, tacrolimus, steroids, and mycophenolate mofetil. Induction therapy consisted of antithymocyte globulins.ResultsThe mean follow-up duration was 7.4 ± 4 years. At 1-year and at last follow-up, 43 patient and death-censored graft survival rates were similar between HLAc and HLAi patients. However, HLAi patients experienced significantly more biopsy-proven rejections compared to HLAc patients. These rejections were predominantly antibody-mediated. Finally, the rate of infectious complications was similar between HLAc and HLAi patients.ConclusionIA in addition to immunosuppression is an effective option for desensitizing HLAi patients, yielding favorable long-term outcomes.